Study on the effects of urea addition on the fermentation quality, nitrogen metabolism, microbial community, and metabolic characteristics of cotton strawlage - Zhou, Shuaibin; Zhu, Zhenxin; Chen, Xiaoping; Pu, Qiuju; Liu, Shuai; Luo, Yuheng; Shao, Yongbin; Sun, Yaoqiang; Sun, Xinwen; Shang, Cuiling; Shen, Wen; Hua, Dengke; et al. (Frontiers in Microbiology, 2025)
BackgroundCotton straw is a widely available agricultural by-product in Xinjiang, China, but its utilization as livestock feed is hindered by challenges such as high fiber content and the presence of toxic free gossypol, which can negatively impact animal health and feed digestibility. Urea addition in feed fermentation has shown potential in improving feed quality by providing a nitrogen source for microorganisms, promoting fiber degradation, and increasing the content of crude protein. However, the optimal urea addition level for cotton straw fermentation remains unclear. The objective of this study was to explore the effects of urea addition on the fermentation quality, nitrogen fractions, bacterial community, and metabolic characteristics of cotton strawlage. The experiment included a control group with 0 % urea added (U0), a 0.1% urea group (U1, 1 g/kg fresh matter), a 0.2% urea group (U2, 2 g/kg fresh matter), and a 0.4% urea group (U3 4 g/kg fresh matter). After 45 days of fermentation, samples of the strawlage were collected and analyzed for their chemical composition, fermentation quality, nitrogen fractions, bacterial community, and metabolic characteristics.ResultCompared to the U0 group, the U3 group significantly increased total nitrogen (TN), non-protein nitrogen (NPN), acetic acid, and propionic acid contents by 17.93%, 0.08%, 13.26%, and 0.01%, respectively, while significantly reducing free gossypol and non-structural nitrogen (NSN) levels by 48.50% and 14.22%, respectively, thereby optimizing the protein composition of cotton straw. Furthermore, the U1 and U2 groups exhibited significant downregulation of metabolites associated with amino acid and energy metabolism pathways, such as L-arginine, L-proline, L-ornithine, and 2-Oxoglutaric acid, compared to the U0 group.ConclusionThe addition of urea significantly altered the fermentation quality, nitrogen fraction composition, microbial community composition, and metabolic profiles of cotton straw.